A contribution to theoretical foundations of critical media and communication studies - Fuchs, Christian (Javnost (Ljubljana), 2009)
The overall aim of this work is to contribute to the discussion of theoretical aspects of critical media and communication theory. A typology of critical media and communication studies is constructed. Example approaches that are based on the commodity hypothesis, the ideology hypothesis, the alternative media hypothesis, and the alternative reception hypothesis are discussed. It is argued that integrative bridging approaches can be found and that a disciplinary matrix can enhance the dialogue about commonalities and differences within critical communication studies.
Keywords: mass media; množični mediji; množično komuniciranje; komunikacije; komunikologija; communication sciences; sociologija komunikacij; teorija komunikacij